Structural and kinematic analysis of the prototype of a folding work table - Isaac Simbaña; Alexander Tirado; Anderson Arias; Xavier Vaca (NOVASINERGIA)
In this investigation, a folding table was proposed to optimize space utilization in a workshop. Utilizing computer-aided design (CAD) software, we performed 3D modeling for each structural element and conducted a static table analysis under an established distributed load. Fixed supports were strategically placed at the contact area with the floor. Through computational simulation using the finite element method, a mesh consisting of 390 558 elements and 497 625 nodes was generated with an excellent mesh quality, characterized by a skewness of 0.2234. The analysis revealed a stress of 209.36 MPa, resulting in a safety factor of 1.84 when utilizing ASTM A36 structural steel as the material. To further validate the design, constraints, and displacements were configured, and a kinematic simulation was conducted to showcase the table's range of motion. This comprehensive study confirms the feasibility of the proposed folding table prototype.